2016
DOI: 10.1016/j.ihj.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

TAVI for aortic regurgitation – India's first case with Corevalve Evolut R

Abstract: Transcatheter Aortic Valve Implantation (TAVI) is a well-described treatment for symptomatic calcific severe aortic stenosis. However, TAVI technology is being increasingly used around the world to treat selected cases of severe aortic regurgitation (AR). One of the main limitations of using TAVI technology for AR is the lack of calcification, which is common in such cases. This makes anchoring of a TAVI prosthesis to the aortic annulus difficult and risks displacement or embolization. However, with the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As the population continues to age, there will be more patients with complex aortic disease. There have been many cases to prove the application of TAVR technology in special conditionsIn [5][6]. In this case, we demonstrates that transfemoral TAVR via TTE for AR patients with chronic type B dissection is a feasible choice.…”
Section: Discussion Andconclusionmentioning
confidence: 70%
“…As the population continues to age, there will be more patients with complex aortic disease. There have been many cases to prove the application of TAVR technology in special conditionsIn [5][6]. In this case, we demonstrates that transfemoral TAVR via TTE for AR patients with chronic type B dissection is a feasible choice.…”
Section: Discussion Andconclusionmentioning
confidence: 70%
“…Only one full report 12 recorded the AR aetiology of its included patients, with the majority of cases due to degeneration (72.1%) with rheumatic heart disease (23.2%) and bicuspid aortic valve (4.7%) accounting for the remainder of the cases. Two case reports 13,14 also recorded AR aetiology, both secondary to infective endocarditis. None of the studies or case reports reported other aortic valve characteristics such as valve calcification or shape.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%